Formulation and Evaluation of a Cleansing Balm Stick Containing Grape Seed Oil as a Candidate Facial Cleanser - Vica Aspadiah; Astrid Indalifiany; Rahmat Muliadi; Asniar Pascayantri; Elvania Dwiyanti Poea (Journal of Pharmaceutical and Natural Resources, 2026)
Cosmetic cleansers function to remove dirt and residual makeup from the skin surface. Cleansing balm is an oil-based cleansing formulation that works through the dissolution of lipophilic compounds on the skin. Grape seed oil (Vitis vinifera L.), which is rich in fatty acids, has the potential to enhance cleansing effectiveness and can therefore be formulated into a cleansing balm stick. This study aimed to evaluate the physical characteristics and cleansing efficacy of a cleansing balm stick containing grape seed oil. The formulations were prepared with varying concentrations of grape seed oil: 0% (F0), 10% (F1), 20% (F2), and 30% (F3). Evaluation of physical characteristics included organoleptic properties, homogeneity, pH, spreadability, and melting point. The cleansing efficacy test was conducted using the NIKKOL method and verified with an oil control film. The results showed that all formulations exhibited good physical characteristics, were homogeneous, and met the required standards for pH, spreadability, and melting point for topical preparations. Formula F2, containing 20% grape seed oil, demonstrated the most optimal cleansing effectiveness, as indicated by the absence of stains or oil residue after rinsing. Based on these findings, it can be concluded that cleansing balm sticks containing 10–30% grape seed oil possess good physical characteristics, with the optimal formulation at 20% concentration showing the best cleansing effectiveness.